Innovative Hemofiltration Approach to Protamine-Induced Shock After Cardiac Surgery in a Low-Resource Environment: A Case Report - Bihariesingh-Sanchit, Rosita; Bihariesingh, Inhya; Nierich, Arno; Voigt, Pieter (Brazilian Journal of Case Reports, 2025)
Protamine sulfate is routinely administered to reverse heparin anticoagulation following cardiopulmonary bypass (CPB). Although generally well tolerated, protamine may elicit severe hypersensitivity reactions, including anaphylaxis. Managing such complications is especially challenging in resource-limited settings where access to blood products and advanced supportive therapies is constrained. A 61-year-old man with multiple comorbidities underwent elective coronary artery bypass grafting (CABG). Following a 50 mg test dose of protamine sulfate after CPB, the patient developed profound hypotension and refractory shock unresponsive to vasopressors. Cardiac arrest ensued, prompting reheparinization and emergent reinstitution of CPB. Protamine was withheld after the second decannulation. Postoperatively, the patient experienced massive hemorrhage ( 7 liters over 3 hours). Autologous blood was salvaged using a gravity-driven hemofiltration system (HemoClear®), with reinfusion of washed, platelet-rich red blood cells. Four units of FFP and albumin were administered. After stabilization, a reduced protamine dose (0.5 mg/kg) was safely administered for 2 hours postoperatively. The patient recovered without recurrence of adverse events. This case illustrates the importance of early recognition and tailored management of protamine-induced hypersensitivity reactions. In low-resource settings, gravity-driven hemofiltration may offer a feasible method of autologous blood salvage during critical hemorrhagic events.